Pengembangan Bahan Ajar Berbasis Pembelajaran Berdiferensiasi Materi "Aku dan Teman-Teman ku” Kelas 2 Sekolah MI Berkah - Muhammad Syabrina; Manda Yani; Wahidah Wahidah; Nadya Lesta Anggraini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research aims to develop differentiated learning-based teaching materials on the material of Me and My Friends for grade II students of MI Berkah. The development of teaching materials is carried out as an effort to accommodate the diversity of abilities, interests, and learning profiles of students in student-centered learning in accordance with the implementation of the Independent Curriculum. The research method used is Research and Development (R&D) with the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques are carried out through observation, interviews, documentation, and questionnaires. The research instrument consisted of a validation questionnaire of material experts, design experts, teacher assessments, and student responses. The results of the study showed that the teaching materials developed obtained a feasible category based on the assessment of material experts of 70.64%, design experts of 54.63%, teacher assessments of 75%, and student responses of 93.61% with the category of very feasible. The results of the T test showed a significance value of < 0.001 which indicates a significant increase in learning outcomes after the use of teaching materials. In addition, the results of the N-Gain analysis showed an increase in learning outcomes with a high category and the effectiveness of the use of teaching materials was in the effective category. Thus, the differentiated learning-based teaching materials developed are declared valid, feasible, and effective to be used in learning the material of I and My Friends in grade II MI Berkah.